PENERAPAN MODEL PEMBELAJARAN FLIPPED PROBLEM BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA DITINJAU DARI ADVERSITY QUOTIENT - Putri, Silvina Aurelia; Sundayana, Rostina (De Fermat : Jurnal Pendidikan Matematika, 2026)
This study aims to analyze the differences in students’ mathematical problem-solving ability scores between the pretest and posttest after the application of the Flipped Problem Based Learning (FPBL) learning model, and to examine the influence of the problem-solving ability scores based on the students’ Aversity Quotient (AQ) levels, namely high, medium, and low categories, on the Two-Variable Linear Equation System material. Data were obtained through test instruments and questionnaires, then processed using the Paired Sample T-test and One Way Anova. The applied approach is quantitative with a one-group pretest-posttest design, and a purposive sampling technique. This study revealed that the low mathematical problem-solving ability of students is caused by the dominance of the teacher-centered learning approach and the lack of activities that facilitate the development of problem-solving abilities. The results of the analysis indicate that the FPBL model has a significant impact on the difference in average pretest and posttest scores on the essay test of students’ mathematical problem-solving abilities, indicated by a significance value below the threshold of 0.05. However, no significant influence was found on students’ mathematical problem-solving abilities when viewed from the AQ level. This is due to the dominant variation in ability scores between individuals within each AQ group, rather than differences in AQ levels themselves. Thus, AQ levels do not contribute substantially to students’ mathematical problem-solving abilities.